(untitled) (Annals of Medical Research, 2021)
Aim: The effects of cardiac surgery and cardiopulmonary bypass on postoperative liver function tests and hyperbilirubinemia in adult patients undergoing open heart surgery were studied, and related literature was reviewed and compared with our results.